Composition of types fishing gear in Barru regency waters in the pandemic time of Covid-19 - Hasmawati Hasmawati; Adam Adam; Muhammad Aras; Salman Salman (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2021)
The potential of marine fish resources in Districts Barru is multi-species, especially pelagic fish. Therefore, in the management and utilization of fishery resources it is very possible for the community to be able to operate various fishing gear. This study aims to determine the composition of the types of fishing gear operated by fishermen in Barru Districts waters of during the pandemic Covid 19. Data collection was carried out from September to October 2020 in around the waters and coastal areas in Barru Districts. This study used a descriptive survey method, by collecting available data (secondary data) in the form of: categories of types and numbers of fishing gears. besides that, field observations will also be carried out. During the pandemic Covid-19, the operation of fishing gear in Barru Districts waters was 13 types of fishing gear, with a composition consisting of four types of fishing gears that were predominantly used, namely 622 drifting gill nets (28.4%), hand lines (21, 7%), Bottom gill nets (19.9%), trolling line (9.6%). Meanwhile, the least used fishing gear was 8 Bagan Tancap (lift net) (0.4%).